Multiple Clones within Multidrug-Resistant Salmonella enterica Serotype Typhimurium Phage Type DT104 - Markogiannakis, Antonis (American Society for Microbiology, 2000)
Six distinct clones were present among Greek multidrug-resistant Salmonella enterica serotype Typhimurium phage type DT104, since isolates belonging to resistance phenotypes including the ACSSuT (ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline) core could be distinguished with respect to their pulsed-field gel electrophoresis patterns, int1 integron structures, and presence or absence of antibiotic resistance genes ant(3")-Ia, pse-1, and tem-1.